STEM literacy profile of junior high school students in Lampung Province, Indonesia. (June 2020) - Ibrohim,; Abdurrahman,; Jalmo, T
Abstract: The 21st-century learning paradigm emphasizes the ability of students to think critically, be able to connect science with the real world, master information technology, communicate and collaborate so everyone must have critical thinking skills, knowledge and digital literacy skills, information literacy, media literacy, and master information technology and communication. This study aimed to describe the literacy profile of STEM (Science, Technology, Engineering, and Mathematics) on junior high school students in daily life. The study was conducted on junior high school students in Lampung Indonesia involving 167 students from 13 public and private schools. The method used in this study was a mixed-method with Sequential Explanatory Strategy. The research instrument used a questionnaire and interview guidelines. The results showed that junior high school students had used or implemented STEM (Science, Technology, Engineering, and Mathematics) in their daily lives even though sometimes they were not aware of it. The lack of practice in learning to use or apply the four STEM domains causes students to find it difficult to use or apply STEM in daily life. Therefore, the STEM approach needs to be maximized in learning especially science so that students can connect the knowledge obtained with reality in daily life.